Study on Accounting Regulation for Business Combinations - Soprych, Maciej (World Bank, Washington, DC, 2016)
Running a business involves continuous growth. Such growth can be organic, stemming from resources created internally in the enterprise. However, in many cases an external development strategy is adopted, based on acquisition of other entities. Such an acquisition may involve creation of a capital group, within which each of the companies maintains its separate legal personality. However, if a capital group is not the optimal form for the given business activity, acquisition of another entity may take form of a business combination. In such case, assets and liabilities of the acquire are directly incorporated into the books of the acquirer. The overriding principle of accounting regulation is primacy of economic substance over legal format. Pursuant to this principle, economic transactions must be recorded in the accounting records in accordance with their economic nature1. In order to determine properly the economic nature of a business combination, an analysis must be performed of economic impacts of such a combination. Economic consequences for merging entities are described in the provisions of commercial law.